The internet of everything from Islamic perspective - Faizi, Ismail; Abubakar Ibrahim, Adamu (IIUM Press, 2021)
Internet of Everything (IoE)isa nexus of“people”, “processes”, “data”, and “things”, promoting closer collaboration and enhanced compatibility for the purpose of accelerating the flow of network connections and the information transference associated with them. Despite the immense success of IOE, it seems as though the system still has a few glitches in the aspects of security and privacy, or data protection. The various uses of IoE in maintaining and retaining specific individual data must be closely monitored, as it may be misused by anonymous entities for malicious purposes. This paper proposes a possible and relevant solutions to counteract these problems and ensure that the solution is working parallel to Islam's solutions from the Holy Quran and the Noble Sunnah of Prophet Muhammad. Hence the paper conceptualized IoE as an evolving new technology that is a vital part of everyday life and Islam as well. Therefore, those IoE characteristic for the applications and services associated value multilayer stack are highlighted in the paper. The interlinked IoE technologies that gives machine-to-machine connectivity anywhere and anytime to communicate, exchange information, and complete an action associating with value-based are also highlighted. Finally, the paper reveals that IoE implementation with due consideration to value-based may usher in various ethical and privacy concern